Altered Global Signal Topography and Its Different Regional Localization in Motor Cortex and Hippocampus in Mania and Depression. (3rd October 2018) - Zhang, Jianfeng; Magioncalda, Paola; Huang, Zirui; Tan, Zhonglin; Hu, Xiwen; Hu, Zhiguo; Conio, Benedetta; Amore, Mario; Inglese, Matilde; Martino, Matteo; Northoff, Georg
Abstract: Bipolar disorder (BD) is a complex psychiatric disorder characterized by dominant symptom swings across different phases (manic, depressive, and euthymic). Different symptoms in BD such as abnormal episodic memory recall and psychomotor activity have been related to alterations in different regions, ie, hippocampus and motor cortex. How the abnormal regional distribution of neuronal activity relates to specific symptoms remains unclear, however. One possible neuronal mechanism of the relationship is the alteration of the global distribution of neuronal activity manifested in specific local regions; this can be measured as the correlation between the global signal (GS) and local regions. To understand the GS and its relationship to psychopathological symptoms, we here investigated the alteration of both GS variance and its regional topography in healthy controls and 3 phases of BD. We found that the variance of GS showed no significant difference between the 4 groups. In contrast, the GS topography was significantly altered in the different phases of BD, ie, the regions showing abnormally strong topographical GS contribution changed from hippocampus (and parahippocampus/fusiform gyrus) in depression to motor cortex in mania. Importantly, topographical GS changes in these regions correlated with psychopathological measures in both depression and mania. Taken together, our findings demonstrate the central importance of GS topography for psychopathological symptoms. This sheds lights on the neuronal mechanisms of specific psychopathological symptoms in BD, and its relevance in the relationship between global and local neuronal activities for behavior in general.